On the existence of a bounded variation solution of a fractional integral equation in L1[0, T] due to the spread of COVID 19 - El-Sayed, Wagdy G.; Abd El-Rahman, Ragab O.; Abd El-Salam, Sheren A.; El Shahawy, Asmaa A. (JOURNAL OF ADVANCES IN MATHEMATICS, 2022)
In this article, we will investigate the existence and uniqueness of a bounded variation solution for a fractional integral equation in the space L1[0, T] of Lebesgue integrable functions.